Study protocol: developing and evaluating an interactive web platform to teach children hunting, shooting and firearms safety: a randomized controlled trial - David C. Schwebel; D. Leann Long; Marissa Gowey; Joan Severson; Yefei He; Katelyn Trullinger (BMC, 2021)
Abstract Background Firearms injuries present a major pediatric public health challenge in the United States. This study protocol describes research to develop and then conduct a randomized clinical trial to evaluate ShootSafe, an interactive, engaging, educational website to teach children firearms safety. ShootSafe has three primary goals: (a) teach children basic knowledge and skills needed to hunt, shoot, and use firearms safely; (b) help children learn and hone critical cognitive skills of impulse control and hypothetical thinking needed to use firearms safely; and (c) alter children's perceptions about their own vulnerability and susceptibility to firearms-related injuries, the severity of those injuries, and their perceived norms about peer behavior surrounding firearms use. ShootSafe will accomplish these goals through a combination of interactive games plus short, impactful testimonial videos and short expert-led educational videos. Methods Following website development, ShootSafe will be evaluated through a randomized controlled trial with 162 children ages 10-12, randomly assigning children to engage in ShootSafe or an active control website. Multiple self-report, computer-based, and behavioral measures will assess functioning at baseline, immediately following training, and at 4-month follow-up. Four sets of outcomes will be considered: firearms safety knowledge; cognitive skills in impulse control and hypothetical thinking; perceptions about firearms safety; and simulated behavior when handling, storing and transporting firearms. Training in both conditions will comprise two 45-min sessions. Discussion If results are as hypothesized, ShootSafe offers potential as a theory-based program to teach children firearms safety in an accessible, engaging and educational manner. Translation into practice is highly feasible. Trial registration The study protocol was registered on 11/10/20 at clinicaltrials.gov ( NCT04622943 ).